Looking beyond digital broadband speeds: Rural British Columbian’s experiences with internet connectivity as a basic necessity - Kathy L. Rush; Cherisse L. Seaton; Angeliki-Iliana Louloudi; Eric P. H. Li; Khalad Hasan (PLoS ONE, 2025)
Aim This study examined the experience of digital connectivity among rural-living British Columbians both with and without access to high-speed Internet at home. Background Evidence indicates that fewer rural communities have access to high-speed Internet compared to urban communities in Canada, despite government commitments to bring high-speed Internet to all British Columbians by 2027. Yet, differences within rural areas relative to those with access to high-speed compared to those with lower speeds remains a relatively unexplored area. Methods A cross-sectional survey of rural British Columbians both with and without high-speed Internet was conducted between October 2023 and April 2024. Closed and open-ended questions gathered participants’ thoughts and experiences with digital technology access and use. Findings Overall, 461 (M age = 56 years, 72% female) rural BC community members (47% with access to 50 + Mbps download speeds) completed the survey. Despite similar overall digital readiness, skill, and confidence using digital technology, those without high-speed Internet were older, more remote-living, reported using fewer connected devices alongside greater frustration with technology, yet had comparable frequency of Internet use except for less streaming compared to those with access to high-speed Internet. Similar themes were found among open-ended responses of both those with and without high-speed Internet access and surrounded: i) the actual and potential benefits of high-speed connectivity, and ii.) disconnects on many levels, but particularly between expectations for and reality of high-speed connectivity. Conclusion Regardless of broadband speed, there were greater similarities than there were differences across rural community participants, with common perceptions of the benefits of connectivity amid experiences with pervasive disconnections on a number of levels.